Dynamic tuning of optical absorbers for accelerated solar-thermal energy storage - Zhongyong Wang (Nature Portfolio, 2017)
Solar-thermal energy storage based on phase-change materials suffers from slow thermal-diffusion-based charging. Here the authors alleviate this issue by introducing optical absorbers and controlling their distribution to accelerate charging process and thus improve solar-thermal energy conversion.